From Kant to Hegel or What is Classic German Philosophy? - Onnasch Еrnst-Оtto (Actual Problems of Mind, 2017)
By involving a broad historical material, the author demonstrates an indirect reception of Kant’s philosophical ideas in Germany — through C.L. Reingold’s critical reviews and the educational content in Tubinger Stift. The paper argues that Kant’s contemporaries and the later followers of Kant interpreted his views diﬀerently, what casts doubts on the idea of a continuous development of classical German philosophy as an evolution from Kant to Hegel.